Doggy day care - Stern, A. J. (Frankly, Frannie, 2010)
Frannie must rethink her dream of becoming a veterinarian after she and Elliott, her future assistant, cause chaos by letting her Aunt Magoo's dog, Bark, loose in a veterinarian's waiting room.